2014
DOI: 10.1074/jbc.m114.558783
|View full text |Cite
|
Sign up to set email alerts
|

Point Mutations in Dimerization Motifs of the Transmembrane Domain Stabilize Active or Inactive State of the EphA2 Receptor Tyrosine Kinase

Abstract: Background: Isolated Eph transmembrane domains (TMD) dimerize in membrane mimetics, but the functional significance of these interactions is unclear. Results: Mutations introduced into the alternative dimerization motifs of the EphA2 TMD induced an opposite effect on receptor activity. Conclusion: Alternative TMD interactions promote either the active or inactive EphA2 conformation. Significance: The involvement of TMD interactions in Eph receptor activity is discovered.The EphA2 receptor tyrosine kinase plays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(67 citation statements)
references
References 47 publications
3
63
1
Order By: Relevance
“…Some studies indicated that the stability of EPHA2 dimers was related with Ser897 phosphorylation . And mutations on SAM and TM domain are reported to affect EPHA2 dimerization . Although none of the mutations found in our study located on SAM or TM domain, their effect on Ser897 phosphorylation may be related with the stability of EPHA2 dimers.…”
Section: Discussioncontrasting
confidence: 55%
“…Some studies indicated that the stability of EPHA2 dimers was related with Ser897 phosphorylation . And mutations on SAM and TM domain are reported to affect EPHA2 dimerization . Although none of the mutations found in our study located on SAM or TM domain, their effect on Ser897 phosphorylation may be related with the stability of EPHA2 dimers.…”
Section: Discussioncontrasting
confidence: 55%
“…This clustering interface involves lateral contacts between both the cysteine-rich domain domains and the ligand-binding domains (18, 19). Second, NMR structures of the isolated EphA2 transmembrane segments in detergent micelles, molecular modeling, and activity studies have suggested that specific receptor-receptor contacts occur between the transmembrane segments in the absence of ligand(56). Third, it can be expected that contacts occur between the kinase domains, as such contacts are likely required for the EphA2 tyrosine phosphorylation that accompanies the dimerization of unliganded EphA2 in transiently transfected HEK293T cells.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24][25][26][27] Eph receptors also undergo clustering within the plasma membrane upon ligand binding in a manner that is stabilized by additional interactions with other ectodomain and cytodomain regions present on the receptor. 6,[28][29][30] The size of the receptor signaling clusters can vary depending on the mobility of ephrins on adjacent membranes and the cell type in question. 31 Eph receptor can also form hetero-oligomer clusters with members of a different receptor subclass.…”
Section: Organization Of Eph Receptors and Ephrins In Epithelial Cellsmentioning
confidence: 99%